Penerapan Asuhan Keperawatan pada Pasien dengan Hipertensi di RSUD Ende: - Dewi, Ulfa Sartika; Doondori, Anatolia Karmelita; Paschalia, Yustina; Cahyani, Sisilia Leny (Poltekkes Kemenkes Kupang, 2025)
Hypertension is a major health problem in developed and developing countries. Hypertension is a non-communicable disease and is the number one cause of death globally (Mahfud et.al, 2019). World Health Organization (WHO) data for 2022 shows that around 1.13 billion people in the world suffer from hypertension. This case study aims to provide nursing care to Mrs. E. E with Hypertension and analyze the gap between theory and real cases. The method used in this scientific paper is the case study method with a nursing care approach which includes assessment, nursing diagnosis, nursing intervention, implementation and nursing evaluation. The results of the case study on Mrs. E. E found BP data 160/90 mmHg, headache, nape felt tense, weakness, CRT>3 seconds Hb 5, 2 g/dl. The nursing problems that arise are: ineffective peripheral perfusion related to increased blood pressure, acute pain related to physical injury agents, activity intolerance related to weakness and risk of decreased cardiac output related to increased afterload. Nursing interventions are carried out based on nursing problems. Implementation was carried out for 3 days and the results of the evaluation were: ineffective peripheral perfusion was resolved, acute pain was resolved, activity intolerance was resolved and the risk of decreased cardiac output was resolved. Every person suffering from hypertension has different signs and symptoms depending on how long the person has suffered and the length of treatment the patient has undergone. Therefore, it is hoped that you will maintain your health and always comply with taking medication